2014
DOI: 10.1016/j.nuclphysb.2014.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of symmetries and consistency relations in the large-scale structure of the universe for non-local bias and modified gravity

Abstract: Consistency relations involving the soft limit of the (n+1)correlation functions of dark matter and galaxy overdensities can be obtained, both in real and redshift space, thanks to the symmetries enjoyed by the Newtonian equations of motion describing the dark matter and galaxy fluids coupled through gravity. We study the implications of such symmetries for the theory of galaxy bias and for the theories of modified gravity. We find that the invariance of the fluid equations under a coordinate transformation th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(98 citation statements)
references
References 78 publications
(91 reference statements)
3
95
0
Order By: Relevance
“…Beyond the linear order in Newtonian dynamics, local biasing models (e.g., [47,48]) are frequently used, in which the galaxy number density fluctuation is a nonlinear function of the matter density fluctuation to be expanded in a Taylor series. At higher order, however, additional non-local terms can be included in biasing [49], and it was shown (e.g., [50][51][52][53]) that consistent renormalization of galaxy bias requires the presence of non-local derivative terms in addition to the local terms. At the second order, the additional non-local term is the contraction s 2 = s ij s ij of the gravitational tidal tensor [49], and its evidence was measured [54] in simulations, where…”
Section: Galaxy Bias In General Relativitymentioning
confidence: 99%
“…Beyond the linear order in Newtonian dynamics, local biasing models (e.g., [47,48]) are frequently used, in which the galaxy number density fluctuation is a nonlinear function of the matter density fluctuation to be expanded in a Taylor series. At higher order, however, additional non-local terms can be included in biasing [49], and it was shown (e.g., [50][51][52][53]) that consistent renormalization of galaxy bias requires the presence of non-local derivative terms in addition to the local terms. At the second order, the additional non-local term is the contraction s 2 = s ij s ij of the gravitational tidal tensor [49], and its evidence was measured [54] in simulations, where…”
Section: Galaxy Bias In General Relativitymentioning
confidence: 99%
“…Some exact results have recently been obtained [24][25][26][27][28][29][30] in the form of "kinematic consistency relations." They relate the (l þ n)-density correlation, with l large-scale wave numbers and n small-scale wave numbers, to the n-point small-scale density correlation, with l prefactors that involve the linear power spectrum at the large-scale wave numbers.…”
Section: Introductionmentioning
confidence: 99%
“…As described in recent works (Kehagias & Riotto 2013;Peloso & Pietroni 2013;Creminelli et al 2013;Kehagias et al 2014a;Peloso & Pietroni 2014;Creminelli et al 2014;Valageas 2014b;Horn et al 2014Horn et al , 2015, it is possible to obtain exact relations between density correlations of different orders in the squeezed limit, where some of the wavenumbers are in the linear regime and far below the other modes that may be strongly nonlinear. These "kinematic consistency relations", obtained at the leading order over the large-scale wavenumbers, arise from the equivalence principle and the assumption of Gaussian primordial perturbations.…”
Section: Consistency Relations For Density Correlationsmentioning
confidence: 99%
“…The reader may then note that redshift-space distortions (RSD) also involve velocities, but previous works that studied the galaxy density field in redshift space (Creminelli et al 2014;Kehagias et al 2014a) found that there is no equal-time effect, as in the real-space case. Indeed, in both real space and redshift space, the long mode only generates a uniform change of coordinate (in the redshift-space case, this shift involves the radial velocity).…”
Section: Comparison With Some Other Probesmentioning
confidence: 99%
See 1 more Smart Citation